Deposition pattern and subcellular distribution of disease-associated prion protein in cerebellar organotypic slice cultures infected with scrapie - Wolf, Hanna; Hossinger, André; Fehlinger, Andrea; Büttner, Sven; Sim, Valerie; McKenzie, Debbie; Vorberg, Ina M. (Frontiers in Neuroscience, 2015)
Organotypic cerebellar slices represent a suitable model for characterizing and manipulating prion replication in complex cell environments. Organotypic slices recapitulate prion pathology and are amenable to drug testing in the absence of a blood-brain-barrier. So far, the cellular and subcellular distribution of disease-specific prion protein in organotypic slices is unclear. Here we report the simultaneous detection of disease-specific prion protein and central nervous system markers in wild-type mouse cerebellar slices infected with mouse-adapted prion strain 22L. The disease-specific prion protein distribution profile slices closely resembled that in vivo, demonstrating granular spot like deposition predominately in the molecular and Purkinje cell layer. Double immunostaining identified abnormal prion protein in the neuropil and associated with neurons, astrocytes and microglia, but absence in Purkinje cells. The established protocol for the simultaneous immunohistochemical detection of disease-specific prion protein and cellular markers enables detailed analysis of prion replication and drug efficacy in an ex vivo model of the central nervous system.